Let's solve each question step-by-step:
Q1: Solve by substitution
Given:
- \( y = 4x - 9 \)
- \( y = x - 3 \)
Since both equations equal \( y \), we can set them equal to each other: \[ 4x - 9 = x - 3 \] Now, solve for \( x \): \[ 4x - x = -3 + 9 \] \[ 3x = 6 \ x = 2 \] Now, substitute \( x \) back into one of the original equations to solve for \( y \): Using \( y = x - 3 \): \[ y = 2 - 3 \ y = -1 \] Thus, the solution is \( (2, -1) \).
Q2: Solve by substitution
Given:
- \( 4x - y = 20 \)
- \( y = -x + 5 \)
From the second equation, substitute \( y \) in the first equation: \[ 4x - (-x + 5) = 20 \] This becomes: \[ 4x + x - 5 = 20 \ 5x - 5 = 20 \ 5x = 25 \ x = 5 \] Now substituting \( x \) back to find \( y \): Using \( y = -x + 5 \): \[ y = -5 + 5 \ y = 0 \] Thus, the solution is \( (5, 0) \).
Q3: Solve the system by graphing
Given:
- \( y = -3x + 4 \)
- \( y = 3x - 2 \)
Let's find the points to graph both equations.
For \( y = -3x + 4 \):
- If \( x=0 \): \( y = 4 \) (Point: (0, 4))
- If \( x=1 \): \( y = 1 \) (Point: (1, 1))
For \( y = 3x - 2 \):
- If \( x=0 \): \( y = -2 \) (Point: (0, -2))
- If \( x=1 \): \( y = 1 \) (Point: (1, 1))
Now graph: Plot the points and draw both lines. The intersection is at \( (1, 1) \), so the solution to the system is \( (1, 1) \).
Q4: Sketch the solution to the system of inequalities
Given:
- \( y \geq 5 - 2x \)
- \( y < -12x + 2 \)
For \( y \geq 5 - 2x \):
- The line \( y = 5 - 2x \) has a y-intercept of 5 and a slope of -2.
- You will shade above this line.
For \( y < -12x + 2 \):
- The line \( y = -12x + 2 \) has a y-intercept of 2 and a slope of -12.
- You will shade below this line.
When shading the regions, the solution set is where the shading overlaps.
Q5: Solve by elimination
Given:
- \( 8x - 6y = -20 \)
- \( -16x + 7y = 30 \)
First, multiply the first equation by 2: \[ 16x - 12y = -40 \] Now we have:
- \( 16x - 12y = -40 \)
- \( -16x + 7y = 30 \)
Add both equations: \[ (16x - 16x) + (-12y + 7y) = -40 + 30 \] \[ -5y = -10 \ y = 2 \] Substituting \( y \) back into one of the original equations to solve for \( x \): Using \( 8x - 6(2) = -20 \): \[ 8x - 12 = -20 \ 8x = -8 \ x = -1 \] Thus, the solution is \( (-1, 2) \).
Q6: Interpret the scenario and create equations
Let \( s \) be the price of a senior citizen ticket and \( c \) be the price of a child ticket.
From Day 1: \[ 3s + 1c = 38 \quad \text{(Equation 1)} \] From Day 2: \[ 3s + 2c = 52 \quad \text{(Equation 2)} \]
Now subtract Equation 1 from Equation 2: \[ (3s + 2c) - (3s + 1c) = 52 - 38 \] This simplifies to: \[ c = 14 \]
Now substitute \( c \) back into Equation 1: \[ 3s + 1(14) = 38 \ 3s + 14 = 38 \ 3s = 24 \ s = 8 \] Thus, the prices are:
- Senior citizen ticket: $8
- Child ticket: $14.
Let me know if you need further explanations!